PENGENDALIAN BENCANA ALAM BANJIR DI KABUPATEN SUMBAWA BARAT - Lalu Budiman; Lalu Mulkan Thariq Akbar (Sekolah Tinggi Pariwisata Mataram, 2023)
Flood natural disasters have caused significant material losses, occurring 4 (four) times between 2000 and 2019 in West Sumbawa Regency. The natural disaster of flooding is one of the hydrometeorological disasters in West Sumbawa Regency. The aim of this research is to examine the control of natural flood disasters in West Sumbawa Regency. The research method used in this research is descriptive qualitative. The Regional Government of West Sumbawa Regency, through the BPBD, has handled natural flood disasters, including taking precautions by building flood control infrastructure such as the Bintang Bano Dam, Tiu Suntuk Dam, and Bronjong in the Rea Watershed and using stilt houses in the West Sumbawa community. The research results show that West Sumbawa Regency is vulnerable to being affected by high rainfall which makes it frequently affected by flood disasters